Impaired Fibrinolytic Capacity in Patients with Inflammatory Bowel Disease - Gris, J C; Schved, J F; Raffanel, C; Dubois, A; Aguilar-Martinez, P; Arnaud, A; Sanchez, N; Sarlat, C; Balmès, J L (Thrombosis and Haemostasis, 1990)
The venous occlusion test was applied to 17 patients with inflammatory bowel disease (IBD; 7 cases of Crohn’s disease, 10 cases of ulcerative colitis). Results were compared to those obtained in 20 healthy matched control subjects. Patients with IBD had significantly decreased t-PA Ag release (p <0.001) and had no significant vWF Ag release. Residual PAI activity was evidenced after venous stasis in the IBD group but not in the control group. Hypofibrinolysis was more important in patients with an evolutive IBD than in patients with IBD in remission. Impaired systemic fibrinolytic capacity might contribute to an increased risk for thromboembolic complications and to the pathogenesis of inflammatory bowel disease.